DNA damage level in lymphocytes and buccal epithelial cells in Narghile smokers and non-smokers in Duhok city-KRG-Iraq - Hishyar Azo Najeeb; Karzan Khowaraham Karim; Galawezh Obaid Othman; Ayad Ahmad Mohammed; Ahmed Mohammed Salih; Soleen Sardar Zuhdi; Dian Jamel Salih (Oral Oncology Reports)
Introduction: There are different ways for Tobacco consumption among smokers. The main three ways for smoking are Cigarettes, Cigar and Narghile (the waterpipie). Narghile smoking has become a very popular habit among youth in different countries around the world. Results: There is higher frequency of micronuclei formation in cigarettes and Narghile smokers compared to control group (7.1 ​± ​0.9, 11.2 ​± ​0.4, and 2.2 ​± ​0.7 respectively). The mean frequency of the DNA fading (Karyolysis) in Narghile smokers was 29-fold higher than non-smokers. The mean frequencies of Karyorhexis buccal cells in Narghile smokers were 1.9-fold higher than non-smokers. The mean of Pyknosis formation was 19-fold greater than non-smokers. More migrated DNA tails were found Narghile smokers compared to controls. The mean of DNA damage measured by ACA was significantly greater (p ​< ​0.0001) than in non-smokers (53.32 ​± ​3.435 ​N ​= ​26 vs. 22.61 ​± ​1.909 ​N ​= ​21, respectively). Narghile smoking increased frequencies of micronucleus formation in buccal cells of Narghile smokers (p ​< ​0.005) compared to cigarettes smokers and non-smokers. The mean of DNA damage measured in peripheral blood cells of Narghile smokers was significantly greater (p ​< ​0.0001) than in non-smokers. Conclusion: In our study we have found direct and accumulative genomic damage effect of smoking in cigarette and Narghile smokers. Narghile smoking causes more DNA damage in buccal cells and in peripheral blood cells. This could be an evidence indicating that there is accumulative effect of Narghile smoking on genomic stability in peripheral blood cells and as well as in buccal epithelial cells.